Fx=-3x-1

Simple and best practice solution for Fx=-3x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Fx=-3x-1 equation:


Simplifying
Fx = -3x + -1

Reorder the terms:
xF = -1 + -3x

Solving
xF = -1 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
3x + xF = -1 + -3x + 3x

Combine like terms: -3x + 3x = 0
3x + xF = -1 + 0
3x + xF = -1

Reorder the terms:
1 + 3x + xF = -1 + 1

Combine like terms: -1 + 1 = 0
1 + 3x + xF = 0

The solution to this equation could not be determined.

See similar equations:

| 7i+(-2-i)= | | -3(x-1)+10=2x-20 | | 64-.05x=0 | | X+8X=130 | | 7-a=6-a | | -2(2s-6)-12=-2(9s+0)-3 | | 3(x-2)+2(x+1)-(1)=0 | | 5x+2+6x+8=10+5 | | -1/6(x-12)+1/3(x+3)=x-7 | | 7+x=3x-13 | | x-5=-3x-5 | | 64-.05x=20 | | 4(5-a)-3(a+4)=10 | | H/4+5=-1 | | 3(x+7)/2=19 | | 5(x+5)=4(x-5)+x | | 25+j/2=15 | | 2(1-1)=3(a+1) | | -3h-11=-5 | | 7x^2-3=60 | | 2z+10=-5 | | 6t+u=63 | | -6x+25y+9=0 | | 4=-2(-3+f) | | k/6-5=-2 | | 6a-4a+6=8-2a | | 4x-10y=6 | | 15x+y=3 | | 0.33x+0.5x+6=11 | | 203-5x=31x+15 | | 4(h+2)=-24 | | (2x)-(3)=6 |

Equations solver categories